2018
DOI: 10.1021/acs.jproteome.8b00367
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Controlled BioID Design for Endogenous Bait Proteins

Abstract: The CRISPR/Cas9 revolution is profoundly changing the way life sciences technologies are used. Many assays now rely on engineered clonal cell lines to eliminate the overexpression of bait proteins. Control cell lines are typically nonengineered cells or engineered clones, implying a considerable risk for artifacts because of clonal variation. Genome engineering can also transform BioID, a proximity labeling method that relies on fusing a bait protein to a promiscuous biotin ligase, BirA*, resulting in the tagg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 72 publications
4
17
0
Order By: Relevance
“…An appropriate VLP control setup, i.e., a representation of the complete VLP proteome in absence of the effector, is indispensable for Virotrap MS-based analysis as VLPs exhibit their own characteristic proteome content [97]. In the context of appropriate BioID controls, it is noteworthy that by using the power of genome editing, Vandemoortele et al designed a method to obtain isogenic cell lines expressing T2A-BirA* bait fusion or its corresponding BirA* control protein, both under the control of the endogenous bait promoter [105]. The method relies on introduction of the T2A-BirA* cassette at the C-terminus of the protein of interest resulting in bicistronic expression of both the bait and BirA*, thereby serving an elegant control setup for isogenic cells obtained by targeting of a Cas9 enzyme, fused to a cytidine deaminase to the T2A autocleavage site, thereby inactivating the T2A peptide sequence resulting in the expression of the bait fusion from its endogenous promoter.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate VLP control setup, i.e., a representation of the complete VLP proteome in absence of the effector, is indispensable for Virotrap MS-based analysis as VLPs exhibit their own characteristic proteome content [97]. In the context of appropriate BioID controls, it is noteworthy that by using the power of genome editing, Vandemoortele et al designed a method to obtain isogenic cell lines expressing T2A-BirA* bait fusion or its corresponding BirA* control protein, both under the control of the endogenous bait promoter [105]. The method relies on introduction of the T2A-BirA* cassette at the C-terminus of the protein of interest resulting in bicistronic expression of both the bait and BirA*, thereby serving an elegant control setup for isogenic cells obtained by targeting of a Cas9 enzyme, fused to a cytidine deaminase to the T2A autocleavage site, thereby inactivating the T2A peptide sequence resulting in the expression of the bait fusion from its endogenous promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of this strategy with the Bio-ID proximity labelling would create a very powerful tool through which even weak and transient interactions could be identified. Interestingly, it has been recently demonstrated that this labelling strategy can be used for proximal protein mapping for endogenous p53 56 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers can target a labeling enzyme to a different organelle or protein complex in addition to the primary target (Hung et al, 2014). Furthermore, isogenic cell lines can be used to avoid differences in transgene expression (Hesketh, Youn, Samavarchi‐Tehrani, Raught, & Gingras, 2017; Vandemoortele et al, 2019). (c) Background due to nonspecific labeling can be reduced by inducibly activating the labeling enzyme (Cho et al, 2017; Kehrer et al, 2016) or using endogenous CRISPR/Cas9 tagging of bait proteins to maintain physiological levels of the labeling enzyme (Long, Brown, & Sibley, 2018).…”
Section: Analysis Of Proteomic Data From Proximity Labeling Approachesmentioning
confidence: 99%